A Critical Analysis of Unfair Business Competition Practices in the Cooking Oil Industry: A Study of the Decision of the Indonesian Competition Commission No. 15/KPPU-I/2022 - Michael Christiaan; Timothy; Kartika Natalia (Devotion : Journal of Research and Community Service, 2026)
This research critically examines unfair business competition practices in the cooking oil industry through an analysis of the Decision of the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha/KPPU) Number 15/KPPU-I/2022. The study is grounded in observable market distortions, reflected in commodity scarcity and significant price increases that cannot be fully explained by normal market mechanisms. This research aims to analyze the dynamics of unfair business competition practices in the cooking oil industry, evaluate the effectiveness of existing regulations under Law Number 5 of 1999, and identify weaknesses in law enforcement, particularly evidentiary challenges and institutional constraints, through a critical examination of the KPPU decision. This research employed a normative juridical method utilizing both a statutory approach and a case approach. The findings indicate that the legal framework under Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition formally provides adequate regulation of cartel practices; however, its implementation remains substantially constrained, particularly with respect to evidentiary challenges and enforcement effectiveness. The Commission’s decision in the case at hand confirms violations in the form of distribution restrictions, yet fails to comprehensively address all indications of cartel conduct. This reflects a persistent gap between legal norms (das sollen) and actual market practices (das sein). Accordingly, strengthening evidentiary mechanisms, institutional capacity, and inter-agency coordination is imperative to enhance the effectiveness of competition law enforcement in Indonesia.